Root crops agroforestry for greening the sustainability of green revolution (International Journal of Agricultural Research, Innovation and Technology, 2018)
Green revolution started at mid of twentieth century was the answer of anxiousness reminded by Malthusian that food scarcity problems in relation with population growth. In concurrence with exploitation of fossil fuel for agriculture mechanization as well as agrochemicals in the form of inorganic fertilizer and pesticide, green revolution by introducing high yielding varieties of cereals and grains was able to nourish the world population by increasing productivity. Indeed, from beginning of mechanization with fossil fuel based as advised by Rudolf Diesel then Arrhenius would be affected to the release of CO2 to the atmosphere and consequently exaggerating climate change as suffered by current and future generations. Under green revolution based on cereals and grains affected forest conversion into open agricultural land, because both commodities are sun-loving crops, which are hate to the shade. On the other hand, to slow the severity of climate change natural forest must be conserved tightly. Entering third millennium demand of food production with ecologically friendly is stronger. Hence, green revolution needs to be amended into greener perspectives. Thus, implementation of agro-forestry into wide range of agro-ecological zone is urgently innovated. Fortunately, shade tolerant of root crops has significant advantage to be developed under agro-forestry. Under shade of forest canopy at basal forest strata, root crops are able to sequester CO2 to be converted into carbohydrate and other compounds to provide food for the dweller. Back to nature is not only a slogan, with root crops under agro-forestry is a reality; fresh root up to 30 t ha-1 can be harvested yearly as the source of food and renewable fuel as well. This potential is very worthy to improve and greening the existing green revolution to be more sustainable.Int. J. Agril. Res. Innov. & Tech. 8 (1): 26-37, June, 2018